Larix sibirica Ledeb. f. candelabriformis L. V. Orlova, V. V. Byalt et G. A. Firsov, forma nova – a new form of Siberian larch from St. Petersburg - Orlova Larisa Vladimirovna; Byalt Vyacheslav Vyacheslavovich; Forsov Gennady Afanasievich (Hortus Botanicus)
A new for science form of Siberian larch Larix sibirica Ledeb. f. candelabriformis L. V. Orlova, V. V. Byalt et G. A. Firsov was found in plantings on the Smolenka river embankment at St. Petersburg. Brief information on the history of introduction of Larix sibirica Ledeb. at  St. Petersburg is provided, the main differences between the new form and the type form are given (the Latin diagnosis is given), type specimens and the place of their storage are indicated. The article is illustrated with color photographs of a living plant on the Smolenka river embankment. The candelabra-shaped form of Siberian larch is very decorative and is of interest for wider introduction into urban landscaping, especially since it easily propagates through grafting onto the type form.